Arboreal Identification Supported by Fuzzy Modeling for Trunk Texture Recognition - Bressane, A.; Fengler, F.h.; Roveda, S.r.m.m.; Roveda, J.a.f.; Martins, A.c.g. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2018)
ABSTRACT Due to the natural variability of the arboreal bark there are texture patterns in trunk images with values belonging to more than one species. Thus, the present study analyzed the usage of fuzzy modeling as an alternative to handle the uncertainty in the trunk texture recognition, in comparison with other machine learning algorithms. A total of 2160 samples, belonging to 20 tree species from the Brazilian native deciduous forest, were used in the experimental analyzes. After transforming the images from RGB to HSV, 70 texture patterns have been extracted based on first and second order statistics. Secondly, an exploratory factor analysis was performed for dealing with redundant information and optimizing the computational effort. Then, only the first dimensions with higher cumulative variability were selected as input variables in the predictive modeling. As a result, fuzzy modeling reached a generalization ability that outperformed some algorithms widely used in classification tasks. Therefore, the fuzzy modeling can be considered as a competitive approach, with reliable performance in arboreal trunk texture recognition.

RESUMO Devido à variabilidade natural da casca arbórea, há padrões de textura em imagens de tronco com valores pertencentes a mais de uma espécie. Logo, o presente estudo analisou o uso da modelagem fuzzy como uma alternativa para lidar com a incerteza no reconhecimento de padrões, em comparação com outros algoritmos de aprendizado de máquina. Para as análises experimentais foram utilizadas um total de 2160 amostras, pertencentes a 20 espécies arbóreas da floresta decídua brasileira. Depois de transformar as imagens do sistema RGB para modelo HSV, 70 padrões de textura foram extraídos com base em estatísticas de primeira e segunda ordem. Na sequência, foi realizada uma análise fatorial exploratória para tratar informações redundantes e otimizar o esforço computacional. Então, apenas as primeiras dimensões com maior variabilidade acumulada foram selecionadas como variáveis de entrada na modelagem preditiva. Como resultado, a modelagem fuzzy alcançou uma capacidade de generalização superior a de algoritmos amplamente usados em tarefas de classificação. Portanto, a modelagem fuzzy pode ser considerada uma abordagem com desempenho competitivo e confíavel no reconhecimento da textura em imagens do tronco arbóreo.
Keywords: soft computing; image processing; pattern matching; bioinformatics; computação não-rígida; processamento de imagens; correspondência de padrões; bioinformática